Peningkatan Hasil Belajar Matematika melalui Penerapan Model Pembelajaran Cooperative Learning Tipe Teams Games Tournament pada Siswa Kelas IV SD Negeri Pepen Tahun Pelajaran 2024/2025 - Qona'ah, Rohmatul; Utaminingtyas, Siwi; Wardhani, Ratri Shinta (Universitas Muhammadiyah Magelang, 2025)
This study was conducted to improve students’ mathematics learning outcomes through the implementation of the Cooperative Learning model of the Teams Games Tournament (TGT) type among fourth-grade students at SD Negeri Pepen in the 2024/2025 academic year. Using a Classroom Action Research (CAR) approach, the study involved 26 students as research subjects. Data were collected through documentation, tests, interviews, and observations. The data were analyzed quantitatively to determine improvements in learning outcomes and qualitatively to evaluate teacher and student activities. The study was considered successful if 75% of students achieved a score of 70 or higher based on the Learning Objective Achievement Criteria (KKTP). The findings indicate that the implementation of the TGT model can improve mathematics learning outcomes. The average student score increased from 47.5 in the pre-cycle to 69.61 in Cycle I and further to 82.3 in Cycle II. In addition, the learning mastery level improved from 11.54% in the pre-cycle to 65.38% in Cycle I and 88.46% in Cycle II. These results demonstrate that the indicators of research success were achieved, indicating that the learning model effectively improved students’ mathematics learning outcomes.